2020
DOI: 10.1101/2020.09.28.316950
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Cellular and ECM Aging on Human iPSC-derived Cardiomyocyte Performance, Maturity and Senescence

Abstract: Cardiovascular diseases are the leading cause of death worldwide and their occurrence is highly associated with age. However, lack of knowledge in cardiac tissue aging is a major roadblock in devising novel therapies. Here, we studied the effects of cell and cardiac extracellular matrix (ECM) aging on the induced pluripotent stem cell (iPSC)-derived cardiomyocyte cell state, function, as well as response to myocardial infarction (MI)-mimicking stress conditions in vitro. Within 3-weeks, young ECM promoted prol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…This indicates that adult PV leaflets may be intended to undergo pathological changes. On the other hand, young PV leaflets and PVICs upregulated many physiological protective proteins/genes, like heat shock protein 90 alpha family class A member 1 (HSP90AA1, related to cellular response and recovery), SPP1 (related to bone resorption), and beclin 1 (BECN1, related to autophagy), which have been demonstrated to be beneficial for directly protecting valve cells or slowing down the pathological progression through a compensatory mechanism [36][37][38][39] . Balaoing et al evaluated hemostatic protein regulation in AV tissues and porcine valve endothelial cells (PVECs) with age and reported that old AV leaflets expressed more von Willebrand factor (vWF), while PVECs from the young age group had more gene expression of vWF 40 .…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that adult PV leaflets may be intended to undergo pathological changes. On the other hand, young PV leaflets and PVICs upregulated many physiological protective proteins/genes, like heat shock protein 90 alpha family class A member 1 (HSP90AA1, related to cellular response and recovery), SPP1 (related to bone resorption), and beclin 1 (BECN1, related to autophagy), which have been demonstrated to be beneficial for directly protecting valve cells or slowing down the pathological progression through a compensatory mechanism [36][37][38][39] . Balaoing et al evaluated hemostatic protein regulation in AV tissues and porcine valve endothelial cells (PVECs) with age and reported that old AV leaflets expressed more von Willebrand factor (vWF), while PVECs from the young age group had more gene expression of vWF 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Cellular function and self-organization rely on the composition of endogenously-generated and tissue-specific ECM, which is continuously remodeled throughout development and can become pathogenic in disease states. For example, cardiomyocyte proliferation, sarcomere length and alignment, and adherence to ECM are significantly different between cardiomyocytes cultured on fetal versus aged decellularized cardiac matrices as well as typical matrix coatings, such as Matrigel, implicating ECM composition as a major regulator of tissue organization and function [24][25][26][27]. Consequently, fibrotic scarring that occurs post cardiac injury influences heart function via pathogenic changes to ECM composition [28].…”
Section: Monolayer Versus Three-dimensional Culturementioning
confidence: 99%